CONTENIDOS DIGITALES Y LA PROMOCIÓN DEL TURISMO RURAL EN LA PROVINCIA DE LOS RÍOS, AÑO 2024 - ASPIAZU OLVERA KATTY JACKELINE (2024)
The purpose of this research work is to know the shortcomings of digital content in the province of Los Ríos, to see how it affects rural tourism due to its limited promotion. For this purpose, interviews were conducted with owners and representatives of places that offer rural tourism in seven cantons of the province being them a representative sample to identify and analyze the failures in digital content and its impact on tourism development, the ultimate goal is to provide recommendations to improve the use of digital tools in the promotion of rural tourism. In addition, implement a self-learning and personal development thus achieving to establish knowledge about the tools and consider the essentials to disseminate information quickly and efficiently.